Redescription of Symphurus diabolicus, a Poorly-Known, Deep-Sea Tonguefish (Pleuronectiformes: Cynoglossidae) from the Galápagos Archipelago - Munroe, Thomas A. (2001)
Symphurus diabolicus, previously known only from the holotype collected in 501 m west of Isla San Cristobal (Chatham Island), Galápagos Archipelago, is re-described based on the holotype (112.6 mm SL) and 19 additional specimens (61.1-123.5 mm SL) recently collected from deep waters around the Galápagos Archipelago. Symphurus diabolicus is characterized by: an elongate body; narrow head with pointed snout; 1-3-2 ID pattern; 106-110 dorsal-fin rays; 89-96 anal-fin rays; 12 caudal-fin rays; 57-59 total vertebrae; 5 hypurals; extremely small scales; no pupillary operculum; large, prominent eyes, with migrated eye near dorsal margin of head; relatively short postorbital head length; relatively long snout and predorsal lengths; black peritoneum visible through abdominal wall on both sides of body; uniform olive green to dark brown ocular-side coloration with series of prominent, darker brown, elliptical to rectangular, blotches (not usually forming crossbands) along body at bases of dorsal and anal fins; and uniformly whitish or light yellow blind side. Symphurus diabolicus appears to be endemic to the Galápagos Archipelago, and is relatively common (captured at 16 different localities) at depths of 308 to 757 m (observed as shallow as 245 m) in this region. Examination of this expanded series of specimens confirms the validity of S. diabolicus and provides characters to distinguish it from S. microlepis Garman, a similar species known only from the holotype taken at approximately 530 m off Pacific Panama.